Healthy Food Identification: Food Cues and Claims Affect Speeded and Thoughtful Evaluations of Food. Issue 7 (7th June 2019) - Bailey, Rachel; Muldrow, Adrienne
ABSTRACT: This study investigated the impact of food claims, food cues, and objective health characteristics on health categorization speed and accuracy, believability of claims and perceptions of health, and taste for food items. One hundred twenty-four young adults were exposed to counterbalanced food item images, which varied by directness of visual food cues, type of food claims (health-related vs. taste-related), and objective healthfulness in a fully crossed design across three different food items. Participants categorized the foods as healthy or unhealthy in a speeded task and evaluated the perception of claim believability and perceptions of health and taste after exposure to images of the food items. Direct visual cues, especially when used with health claims, improved health and taste perception ratings and aided believability of health claims even for objectively unhealthy food products.